2015
DOI: 10.1117/1.jrs.9.096049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Air Force Weather Agency cloud data for assessing single and multiple scattering through clouds at optical wavelengths

Abstract: Downloaded From: http://remotesensing.spiedigitallibrary.org/ on 10/12/2015 Terms of Use: http://spiedigitallibrary.org/ss/TermsOfUse.aspx Abstract. The Air Force Weather Agency (AFWA) has a long history of providing global cloud analyses and forecasts. Until recently, their focus has been on determining the cloud amount and cloud type. Satellite-based World-Wide Merged Cloud Analysis (WWMCA) data provided by the AFWA are analyzed to understand and assess their capability to characterize cloud single scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…(5) Roadcap et al (2015) examined WWMCA for single and multiple scattering through clouds at optical wavelengths. In their analysis, effective cloud optical depth was analyzed in relation to diffuse versus direct transmission for a select number of locations.…”
Section: Cloud Effects Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) Roadcap et al (2015) examined WWMCA for single and multiple scattering through clouds at optical wavelengths. In their analysis, effective cloud optical depth was analyzed in relation to diffuse versus direct transmission for a select number of locations.…”
Section: Cloud Effects Modelingmentioning
confidence: 99%
“…The capability to accurately assess the narrowband or broadband spectral effects of clouds is of particular importance to the intelligence community, yet any existing models and simulations are limited in distribution and highly specialized for particular sensors of interest with limited applicability to the research community. Previous studies have shown the feasibility of using Air Force weather data for characterizing single and multiple scattering through clouds at optical wavelengths (Roadcap et al 2015). This research seeks to describe the development of an integrated internal LEEDR capability leveraging these external datasets relevant to cloud microphysical properties in a nearreal-time environment.…”
Section: Introductionmentioning
confidence: 99%